Population Structure and Single Nucleotide Polymorphism Diversity of Historical Minnesota Maize Inbreds. Issue 4 (1st July 2013) - Schaefer, Christopher M.; Bernardo, Rex
ABSTRACT: The University of Minnesota has developed more than 600 maize ( Zea mays L.) inbreds since 1915. Our objectives were to (i) characterize the population structure and relatedness in the historical Minnesota maize inbred collection in comparison with inbreds of known heterotic groups, (ii) identify any unique germplasm groups among the historical Minnesota inbreds, and (iii) characterize the genetic diversity of the historical Minnesota germplasm. We used the Illumina MaizeSNP50 Beadchip to analyze 284 inbreds with 43, 252 single nucleotide polymorphism markers: 143 inbreds developed at Minnesota (referred to as "A" inbreds), 26 inbreds developed by public breeding programs, and 115 inbreds developed by seed companies. Model‐based clustering divided the inbreds into K = 5 subpopulations represented by the B73, Mo17, Oh43, A321, and PH207 genetic backgrounds. More than 60% of the A inbreds clustered in the A321 subpopulation; many of these inbreds were derived from the open‐pollinated cultivar Minnesota 13. The A321 subpopulation had higher mean dissimilarity (0.384) and gene diversity (0.377) than the other four subpopulations. Subclusters in the A321 and Oh43 subpopulations represented groups of inbreds unique to the historical Minnesota germplasm. Our results may help provide maize breeders with information needed to effectively use historical genetic resources while maintaining heterotic patterns necessary in hybrid breeding.